Class XI Myosins Contribute to Auxin Response and Senescence-Induced Cell Death in Arabidopsis - Ojangu, Eve-Ly; Ilau, Birger; Tanner, Krista; Talts, Kristiina; Ihoma, Eliis; Dolja, Valerian V.; Paves, Heiti; Truve, Erkki (Frontiers in Plant Science, 2018)
The integrity and dynamics of actin cytoskeleton is necessary not only for plant cell architecture but also for membrane trafficking-mediated processes such as polar auxin transport, senescence, and cell death. In Arabidopsis, the inactivation of actin-based molecular motors, class XI myosins, affects the membrane trafficking and integrity of actin cytoskeleton, and thus causes defective plant growth and morphology, altered lifespan and reduced fertility. To evaluate the potential contribution of class XI myosins to the auxin response, senescence and cell death, we followed the flower and leaf development in the triple gene knockout mutant xi1 xi2 xik (3KO) and in rescued line stably expressing myosin XI-K:YFP (3KOR). Assessing the development of primary inflorescence shoots we found that the 3KO plants produced more axillary branches. Exploiting the auxin-dependent reporters DR5::GUS and IAA2::GUS, a significant reduction in auxin responsiveness was found throughout the development of the 3KO plants. Examination of the flower development of the plants stably expressing the auxin transporter PIN1::PIN1-GFP revealed partial loss of PIN1 polarization in developing 3KO pistils. Surprisingly, the stable expression of PIN1::PIN1-GFP significantly enhanced the semi-sterile phenotype of the 3KO plants. Further we investigated the localization of myosin XI-K:YFP in the 3KOR floral organs and revealed its expression pattern in floral primordia, developing pistils, and anther filaments. Interestingly, the XI-K:YFP and PIN1::PIN1-GFP shared partially overlapping but distinct expression patterns throughout floral development. Assessing the foliar development of the 3KO plants revealed increased rosette leaf production with signs of premature yellowing. Symptoms of the premature senescence correlated with massive loss of chlorophyll, increased cell death, early plasmolysis of epidermal cells, and strong up-regulation of the stress-inducible senescence-associated gene SAG13 in 3KO plants. Simultaneously, the reduced auxin responsiveness and premature leaf senescence were accompanied by significant anthocyanin accumulation in 3KO tissues. Collectively, our results provide genetic evidences that Arabidopsis class XI myosins arrange the flower morphogenesis and leaf longevity via contributing to auxin responses, leaf senescence, and cell death.